Building, scaling and spreading community-based transitional care programs—Bold change leadership for evidence-based integrated care. - Giosa, Justine; Saari, Margaret; Fisch, Shelby (International Journal of Integrated Care (IJIC))
Background: Since 205, SE Health has been on a bold change leadership journey to operationalize transitional models of home and community care with 20+ system partners including hospitals and regional health authorities. Join us to learn and share successes, challenges, and opportunities for scale and spread of community-driven integrated care solutions. Audience: As one of Canada largest not-for-profit social enterprises working across the care continuum, SE Health is in a unique position to develop, implement, evaluate, scale, and spread evidence to support meaningful health system change. The SE Research Centre is embedded in SE Health and conducts applied health services research to develop evidence-based solutions to tough health and social care problems. We invite anyone interested in this type of learning health system environment policy leaders, decision-makers, researchers, providers, clients, and families to come together in this workshop around the Quadruple Aim and Health Equity as a common language for transparent dialogue on progress, results, and impact of integrated transitional care programs. Approach: This workshop will begin with an overview (5 minutes) of a scoping review that revealed a need for more evidence to understand the current and future influence of integrated home and community care programs on Quadruple Aim and Health Equity outcomes across the health system. Next, we will present the SE Health case study (20 minutes) of developing and testing transitional models of home and community care, using Quadruple Aim and Health Equity as a frame for sharing about successes and opportunities. Details will include: ) Population Health: Implementation of a comprehensive standardized assessment tool at intake and discharge (interRAI Home Care), with opportunities to maximize use of this data to support goal-oriented care planning and outcome evaluation; 2) Client experience: A primary clinician model design to support continuity, with opportunities to standardize outcome measurement around what matters most to clients and families; 3) Provider Experience: Workforce stabilization through operationalization of a dedicated and salaried staffing model, with room to optimize discipline-specific scopes of practice across interdisciplinary teams; 4) Value: 20+ programs with high volumes that free up hospital beds for people who need them, and a goal to refine program inclusion criteria to better predict service utilization patterns; 5) Equity: Improved client and caregiver access and linkages to publicly-funded community-based care that emphasizes social determinants of health, with opportunities for additional authentic engagement of end-users in program evaluation. For most of the workshop (45 minutes), participants will be divided into small groups and asked to identify micro, meso, and maco system barriers and solutions for further scale and spread of transitional models of home and community care reflecting on the case study and their own experiences. Groups will have an opportunity to consider the following research knowledge products to support their ideation: ) a Holistic Health Needs Report; 2) the Client Experience Survey of Integrated Home and Community Care; 3) The Observe, Coach, Assist and Report framework for team-based care; 4) The Resource Utilization Groups III Home Care (RUG-III-HC) Case Mix Algorithm; and 5) The Participatory Research to Action Framework. Outcomes: In the final part of the workshop (0 minute), small groups will have an opportunity to share back to the larger group one actionable idea to improve evidence-based decision-making in scale and spread of integrated transitional models of home and community care, using the research knowledge product at their table. Facilitators will summarize key takeaways for strategic clarity among funders, decision-makers, researchers, providers, clients and families. At the end of the workshop, participants will have an opportunity to take away summaries and copies of the knowledge products for further consideration in their own change leadership on integrated care.